2015
DOI: 10.1039/c5sm00464k
|View full text |Cite
|
Sign up to set email alerts
|

Tuning assembly and enzymatic degradation of silk/poly(N-vinylcaprolactam) multilayers via molecular weight and hydrophobicity

Abstract: We report on enzymatically degradable nanothin coatings obtained by layer-by-layer (LbL) assembly of silk fibroin with poly(N-vinylcaprolactam) (PVCL) via hydrogen bonding and hydrophobic interactions. We found that both silk β-sheet content, controlled through dipping and spin-assisted LbL, and PVCL molecular weight regulate film thickness, microstructure, pH-stability, and biodegradability with a nanoscale precision. Thickness of (silk/PVCL) films increased with increase in PVCL molecular weight and decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 71 publications
2
31
1
Order By: Relevance
“…The enzymatically degradable multilayers obtained by all-aqueous assembly of PVCL with silk protein have been developed in our laboratory. 51 Silk fibroin amide and hydroxyl groups can participate in hydrogen bonding with carbonyl groups of PVCL lactam ring with hydrophobic stabilization at high pH values. Hydrogen bonding between carbonyls of PVCL and carboxylic groups of silk at acidic pH provided thicker PVCL/silk coatings, while interaction between phenolic groups in silk fibroin and PVCL carbonyls provided much lower thickness at neutral pH due to the ionization of silk acidic groups.…”
Section: Two-and Three-dimensional Coatings Of Pvclmentioning
confidence: 99%
“…The enzymatically degradable multilayers obtained by all-aqueous assembly of PVCL with silk protein have been developed in our laboratory. 51 Silk fibroin amide and hydroxyl groups can participate in hydrogen bonding with carbonyl groups of PVCL lactam ring with hydrophobic stabilization at high pH values. Hydrogen bonding between carbonyls of PVCL and carboxylic groups of silk at acidic pH provided thicker PVCL/silk coatings, while interaction between phenolic groups in silk fibroin and PVCL carbonyls provided much lower thickness at neutral pH due to the ionization of silk acidic groups.…”
Section: Two-and Three-dimensional Coatings Of Pvclmentioning
confidence: 99%
“…Another alternative for fastening the deposition is to include a constant stirring of the solutions during the deposition, which allows limiting the deposition times to 10-20 s [177]. Furthermore, the spray-assisted and spin-assisted deposition methods have gained importance as alternatives to the dipping deposition because they allow a significant reduction on the fabrication time, increasing the homogeneity of the deposited films [178][179][180][181][182].…”
Section: Approaches For Lbl Assembly On Colloidal Surfacesmentioning
confidence: 99%
“…Developing hydrogels that exhibit combined properties of stimuli responsiveness and mechanical properties is of significant interest in the biomedical field. It has been reported that RSF and PVCL form stable hydrogen bonding interactions, which have been applied to fabricate capsules and coatings (16,17). Recently, we reported a facile fabrication of RSF-PVCL hybrid hydrogels by a photochemical crosslinking method (18).…”
Section: Introductionmentioning
confidence: 99%